Collateral Estoppel and Claim Construction Orders: Finality Problems and Vacatur Solutions - Garza, Anthony M. (Science and Technology Law Review, 2005)
Collateral estoppel could be a powerful tool in patent litigation. When a claim construction is necessary to a final judgment, ordinarily, an adverse party may not relitigate the construction in a future action. Current Federal Circuit jurisprudence, however, seems to offer an escape hatch. Because courts often construe patent claims before the trial begins, a party subject to an adverse claim construction could settle to try to avoid any future collateral effects. If a future court cannot determine whether the prior claim construction ruling was “final”, the court will not give the claim construction ruling collateral estoppel effect. Due to the interlocutory and changeable nature of a claim construction order, finality is always in doubt. This article suggests how a future court could find a past claim construction ruling as “final”, despite its tentative nature. A motion for vacatur necessarily determines whether a claim construction ruling is “practically final”, providing enough “finality” to support collateral estoppel in many circuits. To support this conclusion, the article explores current doctrine examining the intersection of vacatur, collateral estoppel, and interlocutory rulings, including claim construction rulings.